Affects in Online Stakeholder Engagement: A Dissensus Perspective. Issue 1 (9th January 2023) - Castelló, Itziar; Lopez-Berzosa, David
Abstract : A predominant assumption in studies of deliberative democracy is that stakeholder engagements will lead to rational consensus and to a common discourse on corporate social and environmental responsibilities. Challenging this assumption, we show that conflict is ineradicable and important and that affects constitute the dynamics of change of the discourses of responsibilities. On the basis of an analysis of social media engagements in the context of the grand challenge of plastic pollution, we argue that civil society actors use mobilization strategies with their peers and inclusive-dissensus strategies with corporations to convert them to a new discourse. These strategies use moral affects to blame and shame corporations and solidarity affects to create feelings of identification with the group and to avoid disengagement and polarization. Our research contributes to the literature on deliberative democracy and stakeholder engagement in social media in the collective constructions of discourses on grand challenges.